A meta-analysis to explore privacy cognition and information disclosure of internet users. (April 2020) - Yu, Lu; Li, He; He, Wu; Wang, Feng-Kwei; Jiao, Shiqiao
Highlights: Identify the differences between privacy concerns and perceived privacy risks based on the Elaboration Likelihood Model. Privacy concern and perceived privacy risks have different effects on privacy disclosure intention and behavior. Platform types moderates the relationships of privacy cognitions and privacy disclosure. Abstract: Based on the Elaboration Likelihood Model (ELM), this study identifies the differences between perceived privacy risks and privacy concern. Furthermore, the study analyses how perceived privacy risks and privacy concerns affect the disclosure intention and the actual information disclosure behavior of Internet users. In addition, the study discusses the moderating effects of platform types, from the perspective of privacy elaboration likelihood. By applying meta-analyses and SEM on 104 independent studies with 42, 256 samples from existing empirical studies, we attempt to systematically reveal the relationship between privacy cognition and information disclosure. The results show that perceived privacy risks can significantly reduce personal information disclosure intention, as well as actual information disclosure behavior. However, privacy concerns only affect disclosure intention, but do not have a significant effect on actual information disclosure behavior. The study also verified that platform types have moderating effects on the privacy decision making of Internet users. The findings yield important and useful implications, both for research and for practice.